A grounded theory research protocol on an attempt to practice interprofessional collaborative care by a primary care clinic health professional fresh graduate in diabetes care - Num, Kelly Sze Fang; Aizuddin, Azimatun Noor; Tong, Seng Fah; Mohamed Said, Mohd Shahrir (Frontiers in Medicine, 2023)
Interprofessional collaborative care (IPCC) can improve the quality of care in patients with chronic diseases in primary care settings. In Malaysia, many medical and healthcare universities have adopted the concept of the interprofessional collaborative practice (IPCP) framework by the World Health Organization (WHO) and implemented interprofessional learning (IPL) in their curriculum to prepare fresh graduates for interprofessional collaboration (IPC) in the health workforce albeit in various degrees. However, there are potential challenges in putting what they have learned into practice, especially in managing chronic diseases due to the complexity of behavior changes required. Diabetes care is a classic example of such chronic disease management. This article presents a qualitative research protocol exploring the processes and challenges of fresh graduates attempting to practice IPC when managing diabetes mellitus (DM) in primary care clinics. A grounded theory (GT) approach will be adopted.